Buck-boost power LED driver using PIC microcontroller - Mohd Taufik, Ab Rahman (2008)
One traditional low-cost way of driving LED in electrical applications uses a resistor in series with the LED device. Although this driving scheme is simple and inexpensive, it suffers several disadvantages. The LED current can vary substantially over the battery voltage range even in normal operation of the device, thus affecting the brightness and reducing the service life of the lighting device. Additionally, protection is needed from automotive voltage transients and reverse polarity. These disadvantages are typically resolved by using constant-current linear regulators. Besides driving the LED at a programmed current, these regulators can inherently protect from a reverse-polarity application and block voltage transients up to tens of volts. Linear current regulators do not require input EMI filters and can yield inexpensive LED driver solutions. However, both the resistor ballasts and the linear regulators exhibit low efficiency. They may become impractical for driving high-brightness LED loads due to the excessive heat dissipation. Therefore, switching power converters are needed for driving many signal and lighting LED devices.